2022
DOI: 10.3390/app12062820
|View full text |Cite
|
Sign up to set email alerts
|

Gonadal Development in European Eel Populations of North Adriatic Lagoons at Different Silvering Stages

Abstract: The European eel (Anguilla anguilla, Linnaeus 1758) is a catadromous fish with significant cultural, scientific, and commercial value. The protection of this species is particularly difficult because the biology of the eel life cycle remains unknown in many aspects. The European eel (A. anguilla) population has declined alarmingly over the past 30 years; this condition has led to questions about the long-term welfare of this species. This work aims to perform a histological analysis on gonad samples from Europ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 39 publications
1
0
0
Order By: Relevance
“…Apparently, the pre-migrant eels of the North Adriatic Sea, if subjected to an artificial reproduction programme, reach sufficient gonadal maturation to give a hormonal response. This is confirmed by the study of Gentile et al [54], which investigated gonadal maturation at the histological level of different silvering eels from the North Adriatic lagoon area, showing that pre-migrant eels, SI III eels, had overlapping oocyte maturation confronted with eels in later stages of maturation. In addition, this early gametogenic activity was found to be associated with accelerated weight growth in the pre-migrating eels studied, a phenomenon normally seen in Atlantic migrant stage IV eels.…”
Section: Discussionsupporting
confidence: 60%
“…Apparently, the pre-migrant eels of the North Adriatic Sea, if subjected to an artificial reproduction programme, reach sufficient gonadal maturation to give a hormonal response. This is confirmed by the study of Gentile et al [54], which investigated gonadal maturation at the histological level of different silvering eels from the North Adriatic lagoon area, showing that pre-migrant eels, SI III eels, had overlapping oocyte maturation confronted with eels in later stages of maturation. In addition, this early gametogenic activity was found to be associated with accelerated weight growth in the pre-migrating eels studied, a phenomenon normally seen in Atlantic migrant stage IV eels.…”
Section: Discussionsupporting
confidence: 60%
“…Kužir et al [54] reported intestine characteristics in eels from the Zrmanja river in Croatia. Gonadal development has been described for lagoons in the North Adriatic by Gentile et al [55]. However, for adequate stock management, it is necessary to investigate all of the mentioned parameters together, especially because fish, compared to other vertebrates, have greater morphological variability within the same species [14,56,57].…”
Section: Introductionmentioning
confidence: 99%